Gabriel Hounds - Stewart, Mary (William Morrow, Co, 1967)
Mary Stewart borrowed freely from the life of Lady Hester Stanhope in this romantic mystery that has people in masquerade, murderers, a poisoning or two, or three and Christy and Charles who cannot decide if they are in love or not. It takes burning the house down for them to decide they ARE in love, while minding assorted animals, including the pigeons and rats of the seraglio
Keywords: Contemporary Literature & Fiction